Productivity Growth and Economic Reform : Evidence from Rwanda - Coulibaly, Kalamogo; Ezemenari, Kene; Duffy, Neal (World Bank, Washington, DC, 2012)
Trade, financial, and exchange rate reforms are shown to have exerted a positive impact on the growth of total factor productivity in Rwanda during the period 1995-2003. Based on a constant returns-to-scale Cobb-Douglas production function, this paper regresses total factor productivity on indices of trade, financial, and exchange rate reforms. The analysis determines that trade reforms and financial reforms each contributed positively to improvements in total factor productivity. The data also suggest that the allocation of official development assistance to human capital made a significant contribution to productivity. In contrast, the appreciation of the real exchange rate of the late 1980's hindered productivity or the growth of TFP. Taken together, the findings for Rwanda presented in this paper show that the strong growth of the past decade has not just been due to a "bounce back" effect following the genocide. The results support the notion that policies favorable to trade development, a deepening of the financial sector, and formation of human capital have been effective for increasing aggregate productivity of the economy and stimulating growth in Rwanda. For sustained growth, the Rwandan authorities should continue to build on these policies, while also taking care to maintain an appropriate exchange rate.